Relationship between Psychological Capital and Organizational Performance Mediated by Organizational Resilience: A Study in District Nowshera, Pakistan - Arshad Iqbal; Shazia Hassan; Kamran Azam (International Journal of Business and Economic Affairs, 2024)
Climate change induced disasters have increased in frequency and intensity threatening economic wellbeing of businesses and communities. Micro, small and medium enterprises (MSME) being integral part of communities makes bulk (90%) of the economic activities around the globe, 96% in Asia and 99% of in Pakistan. In disaster context, survival, recovery and resilience of MSMEs are central to realization of community’s survival, recovery and wellbeing. Small businesses are marred by liability of smallness characterized by limited resources, informal structure and unity of its ownership and management. SMEs are mostly dependent on entrepreneur’s capabilities and resources for management, survival and growth. Some scholar suggest that in MSME context, among other factors entrepreneur’s competencies, psychological and social capitals play a pivotal role in enabling organizational resilience and their disaster performance. Recently few studies have emerged focusing on investigating the impact of various entrepreneurial specific capabilities, resources and mechanisms either on firm resilience or firm performance separately in natural disaster and pandemic context. However, investigating the impact of these on MSME disaster recovery performance in an integrated model seems to be still missing. To address the gap, a study was designed to examine the relationship between entrepreneur’s psychological capital, organizational resilience and MSME disaster recovery performance (MSME-DRP). An empirical quantitative study, grounded in multi-theory perspective, the propositions were explored by collecting data through questionnaire survey from 225 valid responses from flood effected District of Nowshera, Pakistan. Findings revealed that PsyCap significantly and positively impact MSME’s disaster recovery performance. Results further highlighted significant partial mediation by organizational resilience, while it having significantly positive effect on recovery as direct mechanism as well. The paper contributes to the existing stream of research on organizational resilience and organizational disaster performance in broader strategic management literature.